Determinant of Islamic banking institutions's profitability in Malaysia / Muhammad Syafiq Shaharudin - Shaharudin, Muhammad Syafiq (2014)
Nowadays, Islamic banking is one of the important role in banking industry. Many people now more prefer the Islamic banking rather than the commercial bank. Islamic banking already had grown rapidly in Malaysia. There are now total 16 Islamic banks in Malaysia including the foreign bank. There are more researchers started to carry out their research to determine the factors affecting the profit of Islamic banking institutions.